10th Anniversary of Biomedicines—Biomarkers in Pain (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Pain biomarkers are biological indicators or measurable characteristics that can provide information about the presence, severity, or underlying mechanisms of pain. They are valuable for several reasons: Diagnosis and differential diagnosis: Biomarkers can help in the diagnosis of various pain conditions and differentiate between different types of pain, such as neuropathic, inflammatory, or nociceptive pain. This can lead to more accurate and timely diagnoses, which in turn can improve patient care. Monitoring treatment efficacy: Pain biomarkers can be used to track how well treatments are working for individuals suffering from chronic pain conditions. This allows healthcare providers to make informed decisions about adjusting treatment plans, optimizing pain management, and avoiding unnecessary or ineffective interventions. Drug development and testing: Biomarkers play a crucial role in the development of new pain medications and therapies. They can help researchers identify potential drug targets, screen compounds for their pain-relieving properties, and assess the safety and efficacy of experimental treatments in clinical trials. Personalized medicine: Pain biomarkers may, in a future, contribute to treatments, tailored to an individual's unique genetic and biological disposition. Reducing opioid misuse: By using biomarkers to assess pain and treatment responses, healthcare providers can make more informed decisions about opioid prescriptions, potentially reducing the overuse and abuse of these medications.